Evaluating The Association Between Epstein-Barr Virus And Multiple Sclerosis - Bhat, Ankitha G; Nandini P (Gayaku Publisher, 2024)
The highly contagious human herpes virus Epstein-Barr Virus (EBV) affects almost every person at some point in their lifetime. Seroconversion—the production of antibodies—occurs primarily in the early years of life, although it can also happen in adolescence or later in life as a result of EBV infection and the immunological response that goes along with it. Adolescents who contract infectious mononucleosis may experience extensive lymphocytosis, an acute, dangerous illness. Although semen or blood are rarely used in the transmission of EBV, saliva is the primary medium. Strong epidemiological and molecular evidence has been presented in recent research investigations supporting the causal role of EBV in multiple sclerosis (MS). MS is the most common chronic inflammatory and neurodegenerative illness of the central nervous system. It is believed that an infectious agent, primarily Epstein-Barr virus, causes the disease in genetically predisposed individuals. It is unclear how a common virus that usually causes benign latent infections might exacerbate autoimmune diseases and cancer in groups that are already at risk. Here, we summarise the data supporting EBV's role as a causative agent for MS and discuss how different risk variables could impact immunological regulation and EBV infection.